2002
DOI: 10.1023/a:1020970820513
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Extensive variation in the size of the short (heterochromatic) arm of chromosome 14 was found in the wasp Trypoxylon (Trypargilum) albitarse. Ten different variants were differentiated by size and C-banding pattern. Fluorescent in-situ hybridization (FISH) revealed that ribosomal DNA in this species is clustered in the darkly C-banded parts of the heterochromatic short arm of chromosome 14. On this basis, we got an indirect estimate of the amount of rDNA from the area of these dark C-bands. The significant abs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Heteromorphism in size of a particular chromosome pair was found among all metaphases analyzed for homologous chromosomes by mapping 18S rDNA sites. Apparently this is a recurrent characteristic in Meliponini (Rocha et al 2007;Menezes et al 2014;Andrade-Souza et al 2018), and it is due to the repetitive nature of ribosomal DNAs, that results in errors during duplication of the genetic material or uneven crossing-over followed by deletion of a small part of the chromosome (Araújo et al 2002;Mampumbu 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Heteromorphism in size of a particular chromosome pair was found among all metaphases analyzed for homologous chromosomes by mapping 18S rDNA sites. Apparently this is a recurrent characteristic in Meliponini (Rocha et al 2007;Menezes et al 2014;Andrade-Souza et al 2018), and it is due to the repetitive nature of ribosomal DNAs, that results in errors during duplication of the genetic material or uneven crossing-over followed by deletion of a small part of the chromosome (Araújo et al 2002;Mampumbu 2002).…”
Section: Discussionmentioning
confidence: 99%
“…The correlation between NORs and CMA 3 bands is quite common in some insects, including beetles ( Camacho et al 1991 ; Vitturi et al 1999 ; Colomba et al 2000 ; Maffei et al 2001 ; Kuznetsova et al 2001 ; Araújo et al 2002 ; Brito et al 2003 ; Nechayeva et al 2004 ). Silver staining mainly reveals transcriptionally active NORs ( Sumner 1990 ), as opposed to fluorochrome CMA 3 staining which labels NORs independently of their activity ( Schmid and Guttenbach 1988 ).…”
Section: Discussionmentioning
confidence: 99%
“…The absence of a CMA3+/DAPI- block in Trypoxylon lactitarse and Trypoxylon rugifrons in euchromatic regions may be attributed to differences in the molecular composition of the rDNA. Using fluorescent in situ hybridization with an rDNA probe in Trypoxylon albitarse , Araújo et al (2002) found that all rRNA genes are located on the heterochromatic arm in a single chromosome pair.…”
Section: Discussionmentioning
confidence: 99%